2021
DOI: 10.1002/marc.202100281
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X‐Ray Analysis and Morphology Evidence for Stereo‐Assemblies of Periodic Aggregates in Poly(3‐hydroxybutyrate) with Unusual Photonic Iridescence

Abstract: 3D morphology of poly(3-hydroxybutyrate) (PHB), crystallized in the presence of diluents of poly(1,3-trimethylene adipate) and poly(ethylene oxide), is probed using a novel approach coupled with selective etching. For interpreting the mechanisms of crystal periodic aggregation, various microscopic techniques and synchrotron microbeam X-ray analysis are used to observe the top surface in connection with the 3D crystal assemblies. Periodic grating architectures, with the cross-bar pitch exactly matching with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 59 publications
(77 reference statements)
1
28
0
Order By: Relevance
“…Semicrystalline polymers can crystallize into a variety of aggregated patterns with specific orders and morphologies, and it has been shown that polymeric spherulitic textures, assembled by crystal self-assembly, could be precisely tailor-made for potential applications, such as photonic nano- or microstructures. As examples, Zheng et al demonstrated that mesogenic helical architectures could be manipulated to provide a promising avenue toward chiro-optic materials and Yang et al comprehensively reviewed literature work on 3D chiral photonic nanostructures and techniques that may have potential as advanced photonic systems with custom-tailor functionalities. Geng et al prepared poly­( l -lactic acid) (PLLA) forms with selective crystals of shish-kebab architectures on skins and in core layers of spherulites, and this specific morphological arrangement could enhance the mechanical impact toughness and excellent storage modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Semicrystalline polymers can crystallize into a variety of aggregated patterns with specific orders and morphologies, and it has been shown that polymeric spherulitic textures, assembled by crystal self-assembly, could be precisely tailor-made for potential applications, such as photonic nano- or microstructures. As examples, Zheng et al demonstrated that mesogenic helical architectures could be manipulated to provide a promising avenue toward chiro-optic materials and Yang et al comprehensively reviewed literature work on 3D chiral photonic nanostructures and techniques that may have potential as advanced photonic systems with custom-tailor functionalities. Geng et al prepared poly­( l -lactic acid) (PLLA) forms with selective crystals of shish-kebab architectures on skins and in core layers of spherulites, and this specific morphological arrangement could enhance the mechanical impact toughness and excellent storage modulus.…”
Section: Introductionmentioning
confidence: 99%
“…From several recent literature results on other polymers, such as poly(butylene adipate) (PBA), poly(ε-caprolactone) (PCL), and poly([3-hydroxybutyrate] (PHB), poly(nonamethylene terephthalate) (PNT), high-density polyethylene (PE), etc. [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], the periodic morphology is certainly not limited to top surfaces. Still, it also distributes in 3D bulks throughout the entire sample volume.…”
Section: Resultsmentioning
confidence: 99%
“…A few notable examples can be cited here: poly(1,4-butylene adipate) (PBA), poly(ε-caprolactone) (PCL), and poly([β-hydroxybutyrate] (PHB), poly(nonamethylene terephthalate) (PNT), high-density polyethylene (PE), etc. [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. This is a continuous extension of one of our previous works on PPDO [ 35 ].…”
Section: Introductionmentioning
confidence: 99%